Ultra-processed foods and plant-based alternatives impair nutritional quality of omnivorous and plant-forward dietary patterns in college students - Svenja Fedde; Miriam Wießner; Franziska A Hägele; Manfred J Müller; Anja Bosy-Westphal (Scientific Reports)
Abstract The health benefits of a plant-based diet may be outweighed by an increased consumption of ultra-processed foods (UPF) and plant-based alternatives. This study compares diet quality (intakes of protein, saturated fatty acids, sugar, fiber, and micronutrients) and nutritional status (prevalence of low holotranscobalamin and ferritin levels) among different dietary patterns: 22.5% vegans, 46.5% vegetarians, 31% omnivores in 142 first-year college students (20 ± 1.6 years, BMI 21.9 ± 3.1 kg/m², 83% female). Intakes of vitamin B12, folate, iron, zinc, and calcium were on average below reference values, especially in vegans and vegetarians. However, the prevalence of low holotranscobalamin and ferritin levels did not differ between the dietary groups, presumably due to supplementation. Irrespective of the diet, UPF contributed to 49% of daily energy intake. UPF exhibited a lower content of protein, fiber, vitamin B2, vitamin B12, folate, zinc and calcium compared to processed foods (all p < 0.001). Plant-based alternatives contained more fiber and less saturated fatty acids whereas the content of protein and micronutrients was lower compared with animal products (all p < 0.05). In conclusion, UPF consumption contributes to the inadequate intake of many micronutrients by young adults. This is further aggravated by plant-forward eating patterns including the consumption of plant-based alternatives.